Bagaimana Kepatuhan Membayar Zakat? - Muhammad Arfan Harahap; Abd Latip; Iskandar Muda; Andri Soemitra; Sugianto Sugianto (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2021)
The purpose of this study is to investigate the factors that influence trust and knowledge and their impact on compliance in paying zakat, a case study on lecturers who teach in Langkat Regency. The data analysis technique used is the Structure Equation Modeling (SEM) approach based on variance (PLS) with the help of wrapPLS program analysis. This type of research is quantitative, using latent data as a predictor. The research data was obtained by using a questionnaire either in person or online. The findings in this study are the income variable has a positive and significant effect on compliance in paying zakat. Furthermore, the religiosity variable has a positive and significant effect on compliance in paying zakat